Preparación de ácido DL-tartárico 1,4-C14 - Buehler, M.F.; López, Rodolfo; Mitta, A.E.A. (Comisión Nacional de Energía Atómica (CNEA), 1965)
Fil:Buehler, M.F. Comisión Nacional de Energía Atómica (CNEA). República Argentina